(untitled) (Vietnam Journal of Community Medicine, 2026)
This cross-sectional descriptive study aims to describe the current status of some marketing activities for medical services by medical staff at Hanoi Kidney Hospital in 2024. Based on research data from 126 medical staff at Hanoi Kidney Hospital, we found that over 50% of the study subjects were aware of and agreed that the components of the hospital’s medical service marketing were good, useful, enhanced the hospital’s image, and attracted patients. Regarding the characteristics of the study subjects, women predominated (68.25%), and the most common age group was ≤30-39 years old (51.59%). The research subjects were healthcare workers directly involved in clinical and paraclinical departments, meaning those directly involved in patient care and treatment, accounting for 69.05% and playing a significant role in hospital marketing activities. These results show the advantages for marketing medical services at Hanoi Kidney Hospital.